Endovascular embolisation of an iatrogenic superficial temporal artery pseudoaneurysm using liquid embolic. Issue 1 (3rd January 2019) - Entezami, Pouya; Dalfino, John; O'Brien, Michael Wade; Paul, Alexandra
Abstract : Pseudoaneurysms of the superficial temporal artery (STA) are rarely reported consequences of surgical interventions. They carry a high rupture risk and expedient management is required. Both surgical resection and endovascular intervention are available management options. We present the case of a patient with a pseudoaneurysm of the STA, managed by a combination of endovascular embolisation using liquid embolic, followed by surgical resection.